The Key To Deceit: Electra McDonnell # 2 - Weaver, Ashley (New York : Minotaur Books, 2022)
"The second in the Electra McDonnell series from Edgar-nominated author Ashley Weaver, The Key to Deceit, is a delightful World War II mystery filled with spies, murder, romance, and wit. London, 1940. After years of stealing from the rich and giving to the poor-well, to themselves, anyway-Ellie McDonnell and her family have turned over a new leaf as they help the government's war effort. It's true that the straight-laced Major Ramsey didn't give them much choice, but still, Ellie must admit she doesn't miss breaking and entering as much as she might have thought. What she does miss is the challenge of unlocking an impossible code and the adrenaline rush that comes from being somewhere she shouldn't. So when Major Ramsey turns up unannounced with another job, she can't say no. A woman's body has been found floating in the Thames, with a bracelet locked onto her wrist, and a cameo locket attached to it. It's clear this woman was involved in espionage, but whose side was she on? Who was she reporting to? And who wanted her dead?"--.
new book 2023 spring.
Keywords: Thieves; Espionage; Lock picking; Detective and mystery stories; Novels